2013
DOI: 10.1007/s00520-012-1715-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive skin toxicity treatment for anti-EGFR drugs: evaluation of efficacy of skin moisturizers and lymecycline. A phase II study

Abstract: Data show efficacy of preemptive treatment with a well-tolerated profile. A reduction of severe skin toxicities is shown with an increase of grade 1 toxicities, not leading to anti-EGFR dose reduction and with better quality of life for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In 1 study, after preemptive treatment, only 3 patients of 51 reported a moderate effect of skin toxicity on their overall quality of life, as measured using the mDLQI. 89 Similarly, the results from the STEPP trial indicated a reduced mean mDLQI score for patients who received preemptive treatment for dermatologic toxicity compared with those receiving reactive treatment, indicating that reducing the appearance of early skin reactions could have a significant effect on patient perceptions and morale. 30…”
Section: Reviewmentioning
confidence: 98%
“…In 1 study, after preemptive treatment, only 3 patients of 51 reported a moderate effect of skin toxicity on their overall quality of life, as measured using the mDLQI. 89 Similarly, the results from the STEPP trial indicated a reduced mean mDLQI score for patients who received preemptive treatment for dermatologic toxicity compared with those receiving reactive treatment, indicating that reducing the appearance of early skin reactions could have a significant effect on patient perceptions and morale. 30…”
Section: Reviewmentioning
confidence: 98%
“…Jatoi et al, 39 comparing 2 groups of patients treated with anti-EGFR agents (mostly cetuximab) in combination with tetracyclines or placebo, reported the same rate of skin reactions and no difference in QoL. Grande et al, 40 however, evaluating preemptive lymecycline in a phase II study, obtained gratifying results: 27% G2 and no G3 or G4 skin reactions in patients treated with anti-EGFR agents (59% cetuximab).…”
Section: Antibiotic Prophylaxismentioning
confidence: 92%
“…[27][28][29][30][31][32][33][34][35]52,53 Early data on antibiotic prophylaxis also indicate a positive role of tetracyclines. [37][38][39][40][41] The updated Expert Opinion detailed in this article represents the second Italian consensus positions derived from best clinical practices and from the available scientific literature on the treatment of anti-EGFR skin reactions.…”
Section: Antibioticsmentioning
confidence: 99%
“…Preventive measures for acneiform rash include the use of sunscreen and sun protective behavior, (Burtness et al, 2009) and keeping the skin hydrated by using emollients and avoiding long hot showers and irritating soaps (Ouwerkerk and Boers-Doets, 2010). Several phase 2 studies have evaluated the utility of prophylactic oral tetracyclines in combination with topical steroids, sunscreen, and moisturizers for the prevention of the acneiform rash, with overall promising results that demonstrated a reduced incidence of severe rash (Belum et al, 2017, Grande et al, 2013, Kobayashi et al, 2015, Lacouture et al, 2010, Lacouture et al, 2016, Lacouture and Sibaud, 2018, Scope et al, 2007).…”
Section: Targeted Therapiesmentioning
confidence: 99%